Ionic self-assembled derivatives of perylene diimide: Synthesis, aggregated structure and molecular packing behavior. (April 2017) - Li, Mei; Xu, Jia-Ru; Zeng, Yang; Ben, Hai-Jie; Yao, Fang-Lian; Yang, Shuang; Chen, Er-Qiang; Ren, Xiang-Kui
Abstract: A novel perylene diimide material was prepared by ionic self-assembly (ISA) method. The phase behavior and aggregated structures of the complex were then elucidated via a combination of different experimental techniques such as differential scanning calorimetry, one- and two-dimensional X-ray diffraction, UV/Vis absorption spectra, and Fourier transform infrared spectroscopy. The experimental results reveal that the ISA complex possesses multiple thermally-induced phase structures which are sensitive to peripheral chain motions. At room temperature, it can self-assemble into a monoclinic crystalline structure with dimensions of a  = 4.10 nm, b  = 3.70 nm, c  = 0.34 nm, α  =  β  = 90°, γ  = 98.94°. During heating, the complex enters a hexagonal columnar liquid crystalline phase before developing into another monoclinic liquid crystalline phase. Notably, the complex can be well aligned by simple shearing, which shows anisotropic properties in UV/Vis absorption spectra. This property, in combination with the supramolecular structure, makes the complex a promising material for use in polarized optoelectronic devices. Graphical abstract: Highlights: A novel perylene diimide material was prepared by ionic self-assembly method. The complex possesses supramolecular structure with liquid crystallinity. The sequential phase transformations are sensitive to peripheral chain motions. The complex can be aligned by simple shearing and shows anisotropic property.